ANALISIS PROSES FORMULASI PROGRAM PENDIDIKAN GRATIS BERKUALITAS (TISTAS) JAWA TIMUR - Heni Kurnia Setiyani; Lely Indah Mindarti; Sjamsiar Sjamsuddin (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
The Tuition-Free and Good Quality Education Program in East Java is a policy formed by the current Governor of East Java (Khofifah Indar Parawansa) as realization of political promises. Reviewing the background to the policy formulation process and reviewing from side of the regional legal product is felt to be able to provide a meaningful picture and input for interested parties. In addition, it can also be one of the reading materials. This study uses the systematic literature review method. The results of the study show that the policy formulation process has proceeded sytematically. However, when viewed from the regional legal product, there are aspects that need to be reviewed so that the formulation of this policy will be even better if it is decided to be continued by the new Governor in the next period.